ANALISA KESALAHAN DALAM PENERJEMAHAN KITAB AL-BALAGAH AL-WADIHAH KARYA ALI AL-JARIM DAN MUSTAFA AMIN - Ainurrafiq, Faiq (Cendekia: Jurnal Kependidikan Dan Kemasyarakatan, 2015)
Abstract: The overflow of foreign language books and high demands of market with the need of new products, including the translation, makes the quality of translation work has decreased. In this void, a critic on translation is necessary in order to create an atmosphere of critical and dialogical associated with the work of translation. This paper analyzed and discussed errors of translation of the book of al-Balagah al-Wadihah work of Ali al-Jarim and Mustafa Amin. In accord to this, the researcher attempted to know the forms of errors in the results of translation of al-Balagah al-Wadihah, and how the correct form of alternative translation should be. The results showed that the error in the target language sentence structure included the sequence position of sentences. Errors in the use of sentence effectiveness dealt with translating unnecessary text and repetition of words that had been mentioned. Errors in translating vocabulary covered improper equivalent elections, not equivalence of word categories, and inaccuracy of idiom translation. Additionally, errors were also found in the aspect of eliminating vocabulary, phrases, and sentences.Â Ø©ÙØ¹ÙÙ ÙÙØ¥ Ø©Ø¯ÙØ¯ÙØ¬Ø§ Ø©Ø¬ÙØªØ±ÙÙØ§ Ø¨ØªÙÙØ§ ØªØ§Ø¬Ø§ØªÙØ§ ÙÙØ¥ ÙØ§ÙØ³ÙØ£Ø§ ØªØ§Ø¬Ø§ØÙ Ø©ÙØ¨ÙØ¬ÙØ£Ø§ Ø©ØºÙÙØ§Ø¨ Ø©ÙØ±Ø«ÙÙØ§ Ø¨ØªÙÙØ§ Ø¯ÙØ±Ù ØªÙ Ø¯Ø£Â ÙØ¹ ÙØ±Ø§ÙÙØØ§Ù ÙØ¯ÙÙÙØ§ ÙÙØ¬Ø§ ÙÙÙÙØª ÙØ¯ÙØ¨ ÙØ¬ÙØªØ±ÙØ§ Ø¯ÙÙÙØ§ Ø¯ÙØ¬Ù ÙÙØ¥ Ø§Ø°Ù Ø¹ÙØ¯Ù .Ø©ÙÙØ¹Ø¶Ù Ø©ÙÙÙÙ Ø©Ø¬ÙØªØ±ÙØ§ Ø©Ø¯ÙØ¬ÙÂ ÙÙØ·ØµÙÙ ÙØ±Ø§ÙØ¬Ø§ ÙÙØ¹Ù Â« Ø©ØØ¶Ø§ÙÙØ§ Ø©ØºÙØ§Ø¨ÙØ§ Â« Ø¨Ø§ØªÙÙØ§ Ø©Ø¬ÙØ±Øª ÙÙ Ø¡Ø§Ø·Ø®ÙØ£Ø§ ÙÙÙØªØ Ø©ÙØ§ÙÙÙØ§ ÙØ°Ù ØªÙÙØ§Ø .ØªØ§Ø¬ÙØªØ±ÙÙØ§Â Ø©ÙØ·Ø§ÙØªØÙØ§Ø§ Ø©Ø¬ÙØªØ±ÙØ§ Ø¹ÙÙ ÙÙØ¯ÙØªÙ Ø©Ø¬ÙØªØ±ÙØ§ ÙÙ Ø©Ø¹ÙØ§ÙÙØ§ Ø¡Ø§Ø·Ø®ÙØ£Ø§ ÙÙØ¹ Ø±ÙØ«Ø¹ÙØ§ Ø«ØØ§Ø¨ÙØ§ ÙÙØ§Ø ØØ©Ø³Ø§Ø±Ø¯ÙØ§ ÙØ°Ù ÙÙ .ÙÙÙØ£Â Ø¹ÙÙÙ Ø¨ÙØªØ±Øª ÙÙ ØªÙØ§Ù ÙØ¯ÙÙØ§ Ø©ØºÙÙØ§ ÙÙ ÙÙÙØ¬Ø§ Ø¨ÙÙØ§Ø±Øª Ø¡Ø§Ø·Ø®Ø£ ÙØ£ ÙÙ Ø©Ø³Ø§Ø±Ø¯ÙØ§ ÙØ°Ù Ø¬Ø¦Ø§ØªÙÙ .Ø¡Ø§Ø·Ø®ÙØ£Ø§ ÙØ°ÙÙÂ Ø©Ø¯Ø§Ø¹Ø¥Ù ÙØªØ¬ÙØ±Øª ÙÙØ¥ Ø¬Ø§ØªÙØ ÙØ§ ØªÙÙØ§ ØµÙÙØ§ Ø©Ø¬ÙØ±Øª ÙÙ ÙÙÙØª ØØ©ÙØ§Ù Ø¹ÙÙØ§ ÙÙÙØ¬Ø§ ÙØ§Ø¯Ø®ØªØ³Ø§ ÙÙ Ø¡Ø§Ø·Ø®ÙØ£Ø§ Ø§ÙØ£ .ÙÙÙØ¬Ø§Â Ø©ØºÙÙØ§ ÙÙ â Ø©ÙØ¯Ø§Ø±ÙÙØ§ ØªØ§ÙÙÙÙØ§ Ø±Ø§ÙØªØ®Ø§ ÙÙ Ø¡Ø§Ø·Ø®ÙØ£Ø§ ÙÙØ´Øª ØªØ§ÙÙÙÙØ§ Ø©Ø¬ÙØ±Øª ÙÙ Ø¡Ø§Ø·Ø®ÙØ£Ø§Ù .Ø§ÙØ¨Ø§Ø³ Ø©Ø±ÙÙØ°ÙÙØ§ ØªØ§ÙÙÙÙØ§Â ØØªØ§ÙÙÙÙØ§ ÙØ°Ø Ø¨ÙØ§ÙØ¬Ø§ ÙÙ ÙÙØ°ÙÙ ØØ©ÙØÙØ§Ø·ØµÙØ§Ø§ ØªØ§Ø±Ø§Ø¨Ø¹ÙØ§ Ø©Ø¬ÙØ±Øª ÙÙ Ø¡Ø§Ø·Ø®ÙØ£Ø§Ù ØØ©Ø¨Ø³Ø§ÙÙÙØ§ ÙØ±Øº â ÙØ¯ÙÙØ§Â  .ÙÙÙØ¬Ø§Ù Ø¨ÙÙØ§ØªØ±ÙØ§Ù